Large Splenic Abscess: A management challenge - Gurjar, Bhairu Lal; Prajapati, Sahaj; Tuteja, Neeraj; Chaturvedi, Dr Vinita (Iranian Journal of Pediatric Surgery, 2024)
Splenic abscesses are rare in children. Mostly, they present in immunocompromised children or in children with hematological malignancies. In most of the cases these are smaller, isolated or multiple abscesses and are being successfully treated with broad spectrum antibiotics and percutaneous drainage. However, large abscesses pose a management challenge and require a careful decision to go for either total or partial splenectomy. Ultrasound and CT scan both play a crucial role to decide on these larger abscesses which are prone to rupture and can cause septicemia and death. Different organisms have been isolated from these abscesses as bacteria, fungi and atypical bacteria. We report a case of a massive splenic abscess with septicemia managed successfully by timely operative intervention.